Strategies for Whistleblowing: How Civil Society Organizations Intervene in the Process of Blowing the Whistle - Lo Piccolo, Alessandra (PARTECIPAZIONE E CONFLITTO, 2024)
Whistleblowing and collective action have been historically strictly intertwined. However, few works have tried to understand the interrelations between these forms of ethical resistance. The lack of dialogue between these literature strands seems particularly problematic given the contribution of social movement organizations and civil society groups in collecting, articulating, and publicizing the information disclosed by whistleblowers. Whereas Civil Society Organizations (CSOs) constitute crucial whistleblowers' addresses, much remains to be said about how grassroots collective actors strategically intervene in whistleblowing, easing information disclosure, protecting informants, and triggering broader political and social change processes. Focusing on insights from Italy and Spain, the article draws on qualitative interviews, documents, and parliamentary debates to single out three common strategies CSOs adopt to intervene in the whistleblowing process before, during, and after whistleblowers' disclosure: policy input, direct social action, and legal intervention. The article contributes to ongoing discussions in collective action and whistleblowing research, elucidating how CSOs influence the whistleblowing process and discussing their micro- and macro-level consequences.